Reflections on multilevel legitimacy - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2007)
The function of legitimacy is to ensure voluntary compliance with unwelcome exercises of governing authority. Since practically all European law needs to be implemented and enforced by the governments and courts of the member states, the EU does not have to face its citizens directly. It follows that the legitimacy of European governance ought to be conceptualized at two levels. At one level, the legitimacy of member states is decisive for the compliance of individuals and fi rms, regardless of the ultimate origin - international, European or national - of the rules that demand this compliance. At the other level, the legitimacy of the European 'government of governments' is decisive for the voluntary compliance of member states with the obligations imposed on them by the EU. What should be worrying however is the impact which EU governance - especially the rules of negative integration defi ned by politically non-accountable actors - may have on the legitimacy of member states, and ultimately on their capacity to comply. – – Legitimität hat die Funktion, die freiwillige Befolgung unwillkommener Autoritätsakte zu sichern. Da das Europarecht fast vollständig von den Mitgliedstaaten und ihren Gerichten umgesetzt und durchgesetzt werden muss, kommt es nicht zu einer unmittelbaren Konfrontation der EU mit ihren Bürgern. Deshalb sollte auch die Legitimität des Regierens in Europa als Zweistufen-Konzept diskutiert werden. Auf der einen Ebene bestimmt die Legitimität der Mitgliedstaaten die Reaktion der Bürger auf unwillkommene Regeln oder Entscheidungen, ohne dass es dafür auf deren internationale, europäische oder nationale Herkunft ankäme. Dagegen entscheidet die Legitimität der EU als 'government of governments' darüber, ob die Mitgliedstaaten ihrerseits ihre europäischen Verpfl ichtungen freiwillig erfüllen. Anlass zu Besorgnis gibt allenfalls die Rückwirkung des europäischen Regierens - insbesondere der von politisch nicht verantwortlichen Instanzen defi nierten negativen Integration - auf die Legitimität der Mitgliedstaaten und letztlich auf deren Fähigkeit zur loyalen Umsetzung europäischer Regeln.
Keywords: 300